Klinefelter Syndrome: Clinical Spectrum Based on 44 Consecutive Cases from a South Indian Tertiary Care Center - Asirvatham, Adlyne R. (Indian J Endocrinol Metab, 2019)
BACKGROUND: Klinefelter syndrome (KFS) is the commonest chromosomal abnormality, yet remains largely underdiagnosed due to its varied clinical presentation. This study was done to understand the clinical spectrum in our population. AIM: We intended to study the clinical characteristics of children and adults with KFS in our population. We also desired to identify any special features of Klinefelter variants. METHODS: Forty-four patients with karyotype diagnosis of KFS during the time period 2007-2015 were included in this retrospective study. Clinical details and hormonal profile were obtained from hospital information system. RESULTS: Our study population consisted of 17 (38.6%) participants in pediatric age group (age <18 years) and 27 (61.4%) adults. Clinical presentation prompting evaluation in the former group included cardiac anomalies (29.4%), dysmorphism (23.5%), hypogonadism (17.6%), developmental delay (11.8%), tall stature (11.8%), and cryptorchidism (5.9%). Among adults, 16 (59.2%) presented with hypogonadism and 9 (20.4%) had primary infertility. Six children (35.3%) had micropenis and four (three children, one adult) had unilateral undescended testis. Behavioral problems were detected in 19 (43.2%) subjects. Mean follicle stimulating hormone (FSH) and luteinizing hormone (LH) values were 38 IU/mL and 18 IU/mL, respectively. The classical 47 XXY karyotype was detected in 38 (86.4%) subjects and 6 (13.6%) had karyotype consistent with Klinefelter variants. CONCLUSION: KFS was diagnosed only after 18 years of age in two-thirds of patients. Developmental delay, cardiac anomalies, behavioral abnormalities, and intellectual disabilities were the common presentations in pediatric subjects. Adults predominantly presented with hypogonadism. Individuals with Klinefelter variant karyotype sought medical attention predominantly for non-gonadal concerns.